2014
DOI: 10.1021/la501049z
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication by Physisorbed Molecules in Equilibrium with Vapor at Ambient Condition: Effects of Molecular Structure and Substrate Chemistry

Abstract: The effects of physisorbed organic vapor molecules on friction and wear were studied for various materials with different surface chemistries (metals, ceramics, glasses, carbons, polymers) and adsorbed species with distinct functional groups (short linear-chain, branched, and fluorinated alcohols with alkyl chain lengths up to five carbons as well as acetone and n-decane). Friction test results of stainless steel under equilibrium vapor adsorption conditions indicated that the longer chain length of the adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 60 publications
5
63
0
Order By: Relevance
“…This study also showed that the friction coefficient of stainless steel pairs in vapor phase lubrication condition vary slightly depending on the molecular structure of the adsorbing molecule [211]. For the normal alcohol series, the friction coefficient decreases as the alkyl chain length increases.…”
Section: Surface Roughness Effects On Vapor Phase Lubricationmentioning
confidence: 52%
See 3 more Smart Citations
“…This study also showed that the friction coefficient of stainless steel pairs in vapor phase lubrication condition vary slightly depending on the molecular structure of the adsorbing molecule [211]. For the normal alcohol series, the friction coefficient decreases as the alkyl chain length increases.…”
Section: Surface Roughness Effects On Vapor Phase Lubricationmentioning
confidence: 52%
“…This was proven by testing various simple organic molecules on a number of solid materials with different modulus, hardness, and surface roughness (Fig. 13) [211]. Figure 13(a) shows how different pairs of materials gave varying friction coefficients in dry environment.…”
Section: Surface Roughness Effects On Vapor Phase Lubricationmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies argued that intercalated molecules weaken binding forces between the basal planes, allowing easy shear between the planes. However, a recent study on lubrication by physisorbed organic molecules showed that the friction coefficient of one monolayer of organic molecules at sliding interfaces is typically within 0.15-0.2 for most inorganic materials covering a wide range of modulus, hardness, and surface roughness [19,20]. This value is much larger than the friction coefficients of graphite, MoS 2 , and H 3 BO 3 under super-lubricious conditions, suggesting that the interfacial shear of physisorbed molecules does not appear to give super-lubricity.…”
Section: Introductionmentioning
confidence: 99%